Coexistence of a novel NDM-1-encoding MDR plasmid and an IMP-4-encoding IncN-IncU hybrid plasmid in a clinical isolate of Citrobacter freundii BC73 - Liu, Na; Tang, Biao; Wang, Hui; Chen, Xiangyang; Wen, Peipei; Wang, Zhaorui; Chen, Xu; Guo, Xiaobing; Gou, Jianjun; Song, Yinsen (Frontiers in Microbiology, 2024)
Objectives: To investigate the genetic characteristics and transmission mechanism of the NDM-1-, IMP-4-and SHV-12-producing multidrug-resistant (MDR) clinical isolate, Citrobacter freundii BC73. Methods: C. freundii BC73 was isolated from a urine specimen of a urological patient diagnosed with bladder cancer at a Chinese teaching hospital. Antimicrobial susceptibility testing was carried out using DL-120E susceptibility cards and DL-96A system. Whole genome sequencing (WGS) of the isolate was performed using the Illumina and Oxford Nanopore platforms to analyze the genetic context of drug resistance genes and plasmid characteristics. The phylogenetic tree was constructed and visualized by KSNP3.0 software and iTOL5.0 online database. Results: C. freundii isolate BC73 co-carrying blaNDM-1, blaIMP-4 and blaSHV-12 were multidrug-resistant. blaNDM-1 and blaIMP-4 were located on a novel IncFIB-like plasmid, pCFBC1, and an IncN-IncU hybrid plasmid, pCFBC2, respectively. The transferability of blaNDM-1 and blaIMP-4 from C. freundii BC73 to E. coli J53 was successfully demonstrated. The genetic context of the blaNDM-1 and blaIMP-4 genes were ISCR27-groEL-∆groES-cutA-dsbD-trpF-bleMBL-blaNDM-1-∆ISAba125-IS3000 and intI1-blaIMP-4-Kl.pn.13-mobC-IS6100, respectively. Additionally, two extensive transposition units (MGE1 in pCFBC1, MGE2 in pCFBC2) were identified and numerous antimicrobial resistance genes were discovered on it. Conclusions: To our knowledge, our study represents the first characterization of a ST22 C. freundii isolate co-harboring blaNDM-1, blaIMP-4, and blaSHV-12, obtained from a urine sample.The dissemination of this MDR isolate should be of close concern in future clinical surveillance.